Synthesis and Characterization of Cobalt-Doped Carbon Nanotubes - Kazemzadeh, A.; Mehdizadeh Naraghi, B. (Asian Journal of Chemistry, 2012)
Carbon nanotubes have been synthesized using chemical vapour deposition method in a catalytic bed. Catalyst was prepared by a sol-gel method and then methane was introduced to decompose by the catalyst. After purification of the obtained carbon nanotubes, cobalt was introduced to the carbon nanotube bundles. In order to prevent the cobalt oxidation, the experiment was done under 2 × 10-5 torr vacuum. CoCl2 was used as cobalt source and the furnace temperature increased up to 790 ºC. In this temperature, CoCl2 decomposed and cobalt added to the carbon nanotubes as an additive. SEM images show no difference between carbon nanotube structures before and after annealing. XRD and Raman spectroscopy were used to analyze the samples.